077 Long-term safety and efficacy of mexiletine for patients with myotonic dystrophy type 1 and 2. Issue 6 (27th May 2022) - Mousele, Christina; McDonald, Susan; Pitcheathly, Robert; Hanna, Michael; Turner, Christopher; Matthews, Emma; Carr, Aisling
Abstract : Introduction: Myotonic dystrophies type 1 and 2 (DM1 and DM2) are progressive, inherited multisys- tem disorders characterized by muscle weakness, myotonia and life-threatening cardiac dysrythmias. Treatment of myotonia is important for quality of life, mobility, and functional independence. Mexiletine is a sodium channel blocker, which has so far been shown to be effective in myotonia management in non-dystrophic myotonias. However, cardiac side effects are reported. Its long-term safety and efficacy in DM1 has not been established. Methods: 25 patients with DM1 or DM2 have been treated with mexiletine in the NHNN cohort. Efficacy and tolerance was determined by patient report. PR interval, QRS duration and corrected QT interval (QTc) were noted. Results: Mean duration of treatment was 32.9 months. 21/25 patients reported efficacy, 3/25 partial efficacy, and 4/25 discontinued treatment due to gastrointestinal side effects. Mexiletine did not precipitate symptomatic arrhythmia in any patient. Paired assessment of ECG param- eters at baseline and at the highest treatment dose revealed no significant change in PR interval, QRS complex duration, or QTc. Conclusions: This small retrospective analysis suggests long-term efficacy and cardiac safety of mexiletine for treatment of myotonia in patients with myotonic dystrophies. christinamousele92@gmail.com